Timeshare or Club rest as a lever for the development of tourism in the Republic of Uzbekistan - Alisher, Eshtaev; Abdulaziz, Abduganiev (The journal of contemporary issues in business and government, 2021)
This article does discuss an essence of Time Share. Moreover, main purpose of this article is to investigate Time Share and its strengths in order to enhance one of the strategic realms of economy of Republic of Uzbekistan. Consequently, the juxtaposition of views and experience of foreign countriesprovided in this article.